STRATEGI MARKETING PUBLIC RELATIONS SHOWROOM PT HONDA ARISTA SUDIRMAN PEKANBARU DALAM MEMPENGARUHI KEPUTUSAN KONSUMEN - Dea Thania Qodisiyah; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Today there are very rapid progress in the fields of business and commerce in Indonesia, so as to encourage companies to act practical and economic within business to dominate market share. It is basically the final destination to delivery of the product is a consumer, while the condition of consumers are now already able to act logically so that is more selective toward the purchase of goods. With the level of car sales competition in Pekanbaru, showroom PT Honda Arista Sudirman Pekanbaru devise a proper strategy and deemed the most effective this time is to harness the power of Public Relations marketing activities while enhancing the company's image is the marketing and public relations (MPR). This research aims to analyze the strategy of marketing public relations which used by showroom PT Honda Arista Sudirman Pekanbaru in influencing consumer decisions, it is to determine the pull, push, and pass strategy that used, and the obstacles encountered in performing that strategy of marketing public relations.This research uses descriptive qualitative research method. Informants in this research are the branch manager of showroom PT Honda Arista Sudirman Pekanbaru, CCO, Sales and Marketing, consumers and potential consumers by using purposive sampling technique. Data collection techniques are using observations, interviews and documentation.The results of the research showed that strategy of marketing public relations showroom PT Honda Arista Sudirman Pekanbaru which used to influence consumer decisions is the three ways strategy. Three strategies these are pull, push and pass respectively opportunity to influence consumers in making purchasing decisions. However, in implementing this strategy also found some constraints, namely, cost and budget constraints in running the program,the increasing number of competitors in the business world automotive industry,and in structurally CCO(public relations) position does not have its own division stillbelow the general bureau so that it causes the CCO does not have full authority over decisions designed.